Business dynamics, knowledge economy, and the economic performance of African countries - Simplice Asongu; Voxi Heinrich S. Amavilah; Antonio R. Andrés (African Governance and Development Institute (AGDI), 2019)
This paper develops a framework (a) to examine whether or not the African business e nvironment hinders or promotes the knowledge economy (KE), (b) to determine how the KE affects econom ic performance, and (c) how economic performance relates to the inequality-adjusted human socioeconomic development (IHDI) of 53 African countries during the 1996-2010 time period. We estimate the linkages with three related equations. The results support a strong correlation between the dynamics of st arting and doing business and variations in KE. The results also show that there exists a weak link between KE and economic performance. Nonetheless, KE-influenced performance plays a more important role i n socioeconomic development than some of the conventional control variables like foreign direct investment (FDI), foreign aid, and even private investment.
Keywords: L59; O10; O30; O20; O55; 330; Business Dynamics; Knowledge Economy; Economic Performance; Instrumental Variables; Panel Data; Inclusive Growth and Development; Sub-Saharan Africa